Problematika Penegakan Pasal 98 Undang-Undang No. 32 Tahun 2009 Terhadap Tindak Pidana Lingkungan Hidup - Muhamad Nur Hakim Purba; Alwan Hadiyanto; Ciptono Ciptono (JURNAL USM LAW REVIEW, 2025)
A healthy and sustainable environment is a fundamental human right guaranteed by the constitution; however, it continues to be threatened by industrial and plantation activities that disregard environmental quality standards. This condition underscores the urgency of criminal law as a repressive instrument to deter perpetrators of environmental pollution and destruction. The purpose of this study is to conduct a juridical analysis of Article 98 of Law No. 32 of 2009 on Environmental Protection and Management, particularly regarding the legal basis for criminal liability of offenders and the effectiveness of its implementation in judicial practice. The research employs a normative juridical method with a case approach The findings reveal novelty in providing a critical examination of the obstacles to implementing Article 98, especially concerning the difficulty of proving intent, the weak application of corporate criminal liability, and the judicial tendency to focus on individual actors rather than corporate managerial structures. The study concludes that, normatively, Article 98 offers a progressive and proportional legal instrument for environmental protection; however, its practical enforcement remains suboptimal due to technical limitations, institutional capacity, and external interference. This research recommends strengthening the capacity of law enforcement officers through the use of scientific evidence and environmental forensics, ensuring consistent application of corporate criminal liability, and reinforcing judicial independence, so that Article 98 can effectively function as a repressive legal instrument that is fair, effective, and just.   Lingkungan hidup yang sehat dan lestari merupakan hak asasi manusia yang dijamin konstitusi, namun kenyataannya masih sering terancam akibat aktivitas industri dan perkebunan yang mengabaikan standar baku mutu. Kondisi ini menegaskan urgensi instrumen hukum pidana sebagai sarana represif untuk memberikan efek jera kepada pelaku pencemaran maupun perusakan lingkungan. Tujuan penelitian ini adalah untuk menganalisis secara yuridis ketentuan Pasal 98 Undang-Undang Nomor 32 Tahun 2009 tentang Perlindungan dan Pengelolaan Lingkungan Hidup, khususnya terkait dasar pemidanaan terhadap pelaku serta efektivitas penerapannya dalam praktik peradilan. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan kasus. Hasil penelitian menunjukkan adanya kebaruan berupa analisis kritis terhadap hambatan implementasi Pasal 98, meliputi kesulitan pembuktian unsur kesengajaan, keterbatasan penerapan pertanggungjawaban pidana korporasi, serta kecenderungan hakim lebih menitikberatkan pada individu dibanding struktur manajerial perusahaan. Kesimpulannya, Pasal 98 secara normatif telah menyediakan instrumen hukum progresif dan proporsional untuk melindungi lingkungan hidup, namun penerapannya belum optimal akibat faktor teknis, kapasitas aparat, dan intervensi kepentingan. Rekomendasi penelitian ini menekankan pentingnya penguatan kapasitas aparat penegak hukum melalui bukti ilmiah dan forensik lingkungan, konsistensi penerapan pidana korporasi, serta penguatan independensi peradilan agar Pasal 98 benar-benar berfungsi sebagai instrumen represif yang adil, efektif, dan berkeadilan.